The Potential of coral reefs at Penambulai Island, Aru Islands Regency - Abrahamsz, James; Bothmir, Sara Imelda; Retraubun, Alex S.W (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2024)
Penambulai Island, one of the 676 islands in the Aru Islands Regency, is one of Indonesia's outermost small islands and has the status of a Certain National Strategic Area. The coral reefs on this island have been under pressure from human activities and climate influences. Research in the waters of Penambulai aims to analyze the potential of coral reefs. The research was conducted in August 2023. Data collection used the LIT method and data analysis used the English (1997) percent cover formula and the Standard criteria for coral reef damage and condition. The coral reefs around Penambulai Island are extensive, covering over 1,000 hectares. The majority of the reef area (73.76%) is comprised of living organisms, which is a good sign. Hard corals, a crucial reef-building organism, have a significant presence (42.04%). The reef exhibits high species diversity with 51 hard coral species belonging to various families and genera. Despite these positive aspects, the overall health of the coral reefs is considered